A representação do indígena no discurso da Revista Mundo Jovem no período de governo militar no Brasil - Amaral, Janaina Alves de Oliveira Cordeiro do (2016)
This research will have in order to present a study on the representation of the subject indigenous history presented in the discourse of the magazine Mundo Jovem in the 1970s. Magazine Mundo Jovem has its first manifestations printed in 1963, from a group of young people of the Major Seminary Viamão. Thus, while the magazine threw their networks and let their seeds, new readers conquered. Currently the magazine is in educational media. The time frame is explained by the fact that the research subject appears as a problem in only issues of the 70s, a time of continuities and historical ruptures. Continuity of a dictatorial period and breaks some institutions to address the existing government. It is through discourse analysis, which perceives the movement of a speech back to the old to consummate this 70s. Research has shown us up to this point, that the representation of speech that brings the magazine seems to be the representation of a theological discourse, full of symbolic representations of unprotected subjects, clashing with the political discourse of the period.